Potentiostatic Study for the effect Of LAS on the Corrosion Of pure Zinc in 0.01 M HCl solutions - AL-Saadi, K. A.; Al-Safi, S. A-J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A potentiostatic study for the corrosion of pure zinc in 0.01 M HCl was achieved in absence and presence of (linear alkylbenzene solfonate LAS) detergents in a range of concentrations (0-50) mg/L. The electrochemical studies included anodic, cathodic polarization by using potentiostat over temperature rang (293- 323) K.     The mechanism of corrosion rate of pure zinc was suggested by evaluating of Î±a , Î±c , ba , bc , i0 , Rp and the kinetic parameters also calculated ( Ea , A) at the above temperature rang, The thermodynamic of corrosion, corrosion accelerating and corrosion  protecting were investigated by calculating  (âˆ†G, âˆ†H and âˆ†s) values